2020
DOI: 10.3389/fpsyt.2020.537981
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of Dynamic Function in Patients With Bipolar Disorder I and Its Relationship With Executive-Function Deficit

Abstract: Abnormity in brain regional function and interregional cooperation have been linked with the dysfunction during cognitive and emotional processing in bipolar disorder (BD) patients. Recent evidences have suggested that brain function is not static but temporal dynamic. In present study, we aimed to characterize the temporal dynamics of regional function and interregional cooperation in BD and its relationship with executive dysfunction, an important deficit in BD. Resting-state functional MRI was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Simultaneously, since mPFC is a component of DMN, brain regions exhibit strong low-frequency oscillations in a static state, and are thought to focus on internal mental state processes including mutual inductance, autobiographical memory retrieval or imagining the future. The positive correlation between mPFC and executive performance may indirectly demonstrate that the dysfunctions of DMN are closely related to emotional and executive impairment of BD I to some degree [19]. Moreover, BD subtypes differ in brain structure-function relationships.…”
Section: Executive Function Related Neural Abnormalities In Bdmentioning
confidence: 98%
See 2 more Smart Citations
“…Simultaneously, since mPFC is a component of DMN, brain regions exhibit strong low-frequency oscillations in a static state, and are thought to focus on internal mental state processes including mutual inductance, autobiographical memory retrieval or imagining the future. The positive correlation between mPFC and executive performance may indirectly demonstrate that the dysfunctions of DMN are closely related to emotional and executive impairment of BD I to some degree [19]. Moreover, BD subtypes differ in brain structure-function relationships.…”
Section: Executive Function Related Neural Abnormalities In Bdmentioning
confidence: 98%
“…Compared to other subtypes of BD, BDI patients demonstrate unique neural abnormalities related with executive functioning. Previous research showed that Euthymic BDI patients are impaired in verbal memory and executive functioning [19]. According to Liang and colleagues, BDI patients have abnormal DMN temporal dynamics of spontaneous activity, declined PCC-mPFC connection variety and the connection between the medial prefrontal cortex (mPFC) which is the main source of cardiovascular sympathetic neurons and involve in numerous sensorimotor, cognitive, and affective processes.…”
Section: Executive Function Related Neural Abnormalities In Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a previous study demonstrated that dALFF changes are related to changes in EEG band power ( 50 ). Recently, many psychiatric illnesses have discovered a significant change in dALFF, such as MDD ( 51 ), bipolar disorder ( 52 ), Schizophrenia ( 53 ), primary insomnia ( 54 ), and generalized anxiety disorder ( 55 ). For an instance, Staner found that temporal dALFF can predict suicidal thoughts in depressed patients, while static ALFF cannot ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on dALFF have rarely been conducted in patients with BD. Limited to the routine frequency band (0.01–0.1 Hz), two studies found that patients with depressed BD have decreased dALFF values in bilateral PCu/PCC ( Gong et al, 2020a , Luo et al, 2021 ); two studies found that the patients with depressed BD have decreased dALFF values in the left and right temporal/fusiform gyrus ( Sun et al, 2022 , Tian et al, 2021 ); one study found that patients with manic BD have decreased dALFF values in the PCu/PCC ( Liang et al, 2020 ); one study did not distinguish the patients’ mood states and found that the patients have increased dALFF values in the right fusiform, right hippocampus, and right parahippocampus ( Zhang et al, 2021a ). These previous studies suggest that the dALFF in the PCu/PCC may be consistently decreased in patients with BD.…”
Section: Introductionmentioning
confidence: 99%